Respuestas
Respuesta dada por:
1
(4x-9x)*2=7x-5x-9x
8x-18x=7x-5x-9x
9x+5x-7x+8x-18x=1
22x-25x=1
3x=1
1
x=----
3
x=0,3
8x-18x=7x-5x-9x
9x+5x-7x+8x-18x=1
22x-25x=1
3x=1
1
x=----
3
x=0,3
Respuesta dada por:
1
▪Enunciado:
![4x - 9x(2) = 7x - 5x - 9 4x - 9x(2) = 7x - 5x - 9](https://tex.z-dn.net/?f=4x+-+9x%282%29+%3D+7x+-+5x+-+9)
• Resolvemos, reduciendo términos semejantes y despejando la incógnita "x":
![4x - 9x(2) = 7x - 5x - 9 \\ \\ 4x - 18x = 2x - 9 \\ \\ - 14x - 2x = - 9 \: \: \: \: ( - 1) \\ \\ 14x + 2x = 9 \\ \\ 16x = 9 \\ \\ \boxed{\boxed{x = \frac{9}{16} }} 4x - 9x(2) = 7x - 5x - 9 \\ \\ 4x - 18x = 2x - 9 \\ \\ - 14x - 2x = - 9 \: \: \: \: ( - 1) \\ \\ 14x + 2x = 9 \\ \\ 16x = 9 \\ \\ \boxed{\boxed{x = \frac{9}{16} }}](https://tex.z-dn.net/?f=4x+-+9x%282%29+%3D+7x+-+5x+-+9+%5C%5C++%5C%5C+4x+-+18x+%3D+2x+-+9+%5C%5C+%5C%5C+++-+14x+-+2x+%3D++-+9+%5C%3A++%5C%3A++%5C%3A++%5C%3A+%28+-+1%29+%5C%5C++%5C%5C+14x+%2B+2x+%3D+9+%5C%5C++%5C%5C+16x+%3D+9+%5C%5C++%5C%5C+++%5Cboxed%7B%5Cboxed%7Bx+%3D++%5Cfrac%7B9%7D%7B16%7D+%7D%7D)
• Resolvemos, reduciendo términos semejantes y despejando la incógnita "x":
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años